Estudio de coordinación de protecciones para el sistema eléctrico de la empresa de balanceados PROBALBEN CIA.LTDA. - Bustamante Pilco, Jarlinton Alberto (2022)
The present technological proposal consisted in carrying out the electrical protection coordination study in the company PROBALBEN CIA.LTDA. The current electrical system was characterized by recording loads and field measurements in the factory, in order to tabulate technical data and model the current electrical circuit by using specialized software for industrial electrical systems, which allows simulations of short-circuit currents, load flows and generate the selectivity of coordination of protections. With the application of the software, minimum and maximum short-circuit current values were recorded to verify the performance of the protection equipment. In addition, voltage drops were recorded by processes in the manufacturing of the balance, identifying three critical processes that affect the electrical circuit. The behavior of the thermomagnetic protections, fuses and thermal relays was also analyzed in order to obtain the operation times in the performance during a fault. The results obtained showed that in some points of the network there are voltage drops that exceed the 5% established by the NEC/NFPA 70 standards, problems with the protections which should be replaced, given all these anomalies we proceeded to propose a new scheme of protections considering the established standards and criteria of selectivity of protections, reducing the voltage drops of the affected areas not exceeding the 5%, and it was possible to adjust the operating time to 0. 03 seconds for each protection resulting in a reduction of the production downtime.